Warisan Afiks Bahasa Bali Kuno dalam Bahasa Bali Moderen - Sulibra, I Ketut Ngurah; Erawati, Ni Ketut Ratna; Sutika, I Nyoman Duana (Humanis, 2022)
The Old Balinese language is the forerunner of the existence of the current Modern Balinese language. As an agglutinative language, affixes are important in the formation of vocabulary. There are some Old Balinese affixes inherited in the Modern  Balinese language, both prefixes, infixes, and suffixes. The purpose of this research is to describe the inheritance of Old Balinese language affixes into Modern Balinese language. The theory used is the structural theory. Methodologically, this research is divided into three stages. The first stage of data collection is the library, listening, and note taking method assisted by translation and equivalent techniques. Second, the data analysis phase uses qualitative-quantitative methods with analytical descriptive techniques. Third, the stage of presenting the results of the analysis with the formal-informal method. The results of this study indicate that the inherited Old Balinese language affixes include prefixes reaching 50%, infixes 66, 67 %, and suffixes 42, 86%. It means that there are some Old Balinese language affixes that have not been inherited. Although the Old Balinese language is the source of the existence of the Balinese Modern language, it turns out that not all of its affixes are inherited.